Peningkatan Hasil Belajar Siswa Melalui Ketrampilan Proyek - Suyono Suyono (Syntax Idea)
Learning in the subject of Entrepreneurship at the Senior High School level, especially in class XII MIPA2 at SMA N 2 Madiun, still encounters several challenges. This can be seen from the level of student delays in starting, the completeness of materials, skills in assembling materials, and the completion stage in the product-making process. The general objective of this research is to describe the effectiveness of implementing the Project Skills method for students in Class XII MIPA2 at SMA Negeri 2 Madiun. This research is an action research, as it is conducted to solve learning problems in the classroom. The research was carried out in Class XII MIPA2 at SMA Negeri 2 Kota Madiun, in the odd semester of the 2022/2023 academic year. The study was conducted from September to November in the odd semester of the 2022/2023 academic year. The subjects of the study were students in Class XII MIPA2 at SMA Negeri 2 Kota Madiun in the 2022/2023 academic year. The methods used to collect data in this research were observation, tests, and questionnaires. The results of the study show that the implementation of the Project Task model in the subject of local craft products in Class XII MIPA2 at SMA Negeri 2 Madiun is effective in improving the process skills in completing project tasks in the Entrepreneurship subject.